Innovation, external technological environment and the total factor productivity of enterprises. (17th March 2021) - Xiao, Zumian; Peng, Hongfeng; Pan, Zheyao
Abstract: In this paper, we study the impact of endogenous innovation and the external technological environment on total factor productivity. We first develop an endogenous growth model and derive a testable empirical model. We then estimate the empirical model based on the World Bank's worldwide enterprise survey data for 119 countries spanning 2007–2017. Our results suggest that: (i) enterprises' R&D activity increases their total factor productivity; (ii) a higher level of external technology weakens the impact of the R&D activity on total factor productivity; and (iii) enterprises located in low‐ and middle‐income countries often lack continuous innovation.